1999
DOI: 10.1021/la981011x
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Grafted Polymeric Filters for Chemical Sensors:  Hyperbranched Poly(acrylic acid) Films Incorporating β-Cyclodextrin Receptors and Amine-Functionalized Filter Layers

Abstract: We report a new “molecular-filter” approach for enhancing the selectivity of chemical sensors. Specifically, we describe electrochemical sensors prepared from Au electrodes coated with β-cyclodextrin-functionalized, hyperbranched poly(acrylic acid) (PAA) films capped with a chemically grafted, ultrathin polyamine layer. The hyperbranched PAA film is a highly functionalized framework for covalently binding the β-cyclodextrin molecular receptors. The thin, grafted polyamine overlayer acts as a pH-sensitive “mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 27 publications
1
40
0
1
Order By: Relevance
“…4). Also, dendrimers [227][228][229][230][231][232][233][234]380) are reported to deposit well, as are hyperbranched polyelectrolytes 134,135,141) (cf. Fig.…”
Section: Polymers Suited For Esamentioning
confidence: 99%
See 1 more Smart Citation
“…4). Also, dendrimers [227][228][229][230][231][232][233][234]380) are reported to deposit well, as are hyperbranched polyelectrolytes 134,135,141) (cf. Fig.…”
Section: Polymers Suited For Esamentioning
confidence: 99%
“…Treatment with various functionalized silanes, such as trialkoxy-3-aminopropylsilane 113,114,143,200,219,227,286,388,395) , provides an additional, "easy" access to positively charged surfaces. In a similar way, treatment of gold with functionalized thiols or disulfides, respectively, enables the tailoring of both positively (e. g. when applying cysteamine 119,211,277,296,387) ) or negatively (e. g. when applying mercaptoundecanoic acid 115,116,228,269,286,396,397) ) charged surfaces. As discussed above, film growth is characteristic for a chosen pair of polyelectrolytes and its "matching", and on the conditions for adsorption.…”
Section: Useful Substratesmentioning
confidence: 99%
“…Indeed, while we did successfully develop chemistry to prepare carboxamide and ester derivatives of these hyperbranched PAA grafts, the products of this chemistry were mixtures of carboxylic acids and carboxylic acid derivatives due to incomplete conversion of the PAA carboxylic acid groups. 4,9,10 This was not a problem in cases where the objective was further grafting or introduction of a spectroscopic label (e.g., a pyrene group). 4 It is a concern if quantitative conversion of functional groups is desired.…”
Section: Resultsmentioning
confidence: 99%
“…In the first scheme, the hydroxyl groups of a reduced film were converted to trichloroacetate esters. We had earlier used the Mn 2 (CO) 10 -promoted radical polymerization of such esters in surface modification. 19 This graft chemistry also works with these films.…”
Section: Radical Grafting Onto Poly(allyl Alcohol)-containing Hyperbrmentioning
confidence: 99%
“…Similarly, they have demonstrated that by controlling the pH of a solution, dendrimers can act as molecular-gates admitting molecules on the basis of overall charge. 186,187 Bruening and co-workers have examined the size-based selectivity of Pd NPs embedded in multilayered polyelectrolyte films in hydrogenation of mono-, di-, and tri-substituted alkenes. [180][181][182] These catalysts showed remarkable intramolecular selectivity in the hydrogenation of alkenes based on the degree of substitution of the double bond.…”
Section: Introductionmentioning
confidence: 99%